Theoretical and numerical analyses of composite cylinders subjected to the low velocity impact. (15th October 2019) - Rafiee, Roham; Ghorbanhosseini, Amin; Rezaee, Shiva
Abstract: The main objective of this research is to develop a theoretical solution for predicting the low-velocity impact induced failure in composite cylinders. Observing both in-plane and out-of-plane impact induced failure modes in composite cylinders is demanded of determining all components of the stress and strain fields. Thus, it is necessary to exploit the appropriate theory for this purpose. Layer-wise theory is employed to develop a theoretical solution for extracting stress/strain components in a composite cylinder subjected to low-velocity. Then, proper failure criteria are employed to predict the failure caused by impact. Finally, finite element modeling is performed to analyze the low-velocity impact in composite cylinders. Comparing the results, it is revealed that developed theoretical solution is more accurate than finite element modeling.